2020
DOI: 10.14814/phy2.14404
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic gas compression during forced expiration is greater in men than women

Abstract: Intrapleural pressure during a forced vital capacity (VC) maneuver is often in excess of that required to generate maximal expiratory airflow. This excess pressure compresses alveolar gas (i.e., thoracic gas compression [TGC]), resulting in underestimated forced expiratory flows (FEFs) at a given lung volume. It is unknown if TGC is influenced by sex; however, because men have larger lungs and stronger respiratory muscles, we hypothesized that men would have greater TGC. We examined TGC across the “effort‐depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…expiratory flow limitation), leading to thoracic gas compression. As a result, forced expiratory flows measured at the mouth may be underestimated, particularly at effort independent lung volumes (Guenette et al 2010, Gideon et al 2020. Furthermore, Gideon et al (2020) demonstrated that males show more thoracic gas compression than females due to greater expiratory pressure generation throughout the FVC manoeuvre secondary to greater respiratory muscle mass and power (Gideon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…expiratory flow limitation), leading to thoracic gas compression. As a result, forced expiratory flows measured at the mouth may be underestimated, particularly at effort independent lung volumes (Guenette et al 2010, Gideon et al 2020. Furthermore, Gideon et al (2020) demonstrated that males show more thoracic gas compression than females due to greater expiratory pressure generation throughout the FVC manoeuvre secondary to greater respiratory muscle mass and power (Gideon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, forced expiratory flows measured at the mouth may be underestimated, particularly at effort independent lung volumes (Guenette et al 2010, Gideon et al 2020. Furthermore, Gideon et al (2020) demonstrated that males show more thoracic gas compression than females due to greater expiratory pressure generation throughout the FVC manoeuvre secondary to greater respiratory muscle mass and power (Gideon et al 2020). The relatively lower transpulmonary pressure during tidal breathing results in less thoracic gas compression facilitating greater expiratory flows (Yuan et al 2014).…”
Section: Discussionmentioning
confidence: 99%